2013
DOI: 10.1111/eea.12119
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Sirex noctilio and S. nigricornis emergence using degree days

Abstract: The study of temporal interactions between native insects and alien invaders can be facilitated by the ability to forecast adult emergence. We used field-collected adult emergence data of Sirex noctilio Fabricius (Hymenoptera: Siricidae), a woodwasp native of Eurasia that has recently invaded northeastern North America, and Sirex nigricornis Fabricius, a woodwasp native to North America, to develop and test cumulative degree-day (CDD) models. Five data sets were collected each in Ontario, Canada (S. noctilio) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
(59 reference statements)
3
23
0
Order By: Relevance
“…Emergence began in early Oct and ceased in mid-to late Dec, which agrees with other reports of Sirex emergence in the Southeast (Haavik et al 2013). A test of parallelism found significant differences among years (F = 48.621; df = 8; P < 0.0001), and a final model ( Fig.…”
Section: Combined Yearssupporting
confidence: 91%
See 1 more Smart Citation
“…Emergence began in early Oct and ceased in mid-to late Dec, which agrees with other reports of Sirex emergence in the Southeast (Haavik et al 2013). A test of parallelism found significant differences among years (F = 48.621; df = 8; P < 0.0001), and a final model ( Fig.…”
Section: Combined Yearssupporting
confidence: 91%
“…However, if this trend of higher winter temperatures continued over several years, we might expect to see earlier emergence of natives if they follow the same early patterns as S. noctilio does in consistently warmer temperatures. Zylstra et al (2010) showed that 79% of captured S. noctilio were collected in New York, USA, by the beginning of Aug and all S. noctilio had been captured by the end of Sep. Haavik et al (2013) found S. noctilio emerging from Jul through Sep in Ontario, Canada, and their findings are consistent with additional studies (e.g., Myers et al 2014), which predict future S. noctilio emergence in the Southeast occurring as early as mid-Apr. These patterns indicate that S. nigricornis and S. noctilio will not overlap in seasonal flight patterns, even in the warmer climate of the Southeast.…”
Section: Discussionsupporting
confidence: 78%
“…Sirex noctilio has a temporal advantage over S. nigricornis as many emerge 1-2 months before S. nigricornis, although there is overlap in emergence between these species in northeastern North America (Ryan et al 2012a;Haavik et al 2013;Hartshorn et al 2016;Suppl. material 1: B).…”
Section: Comparing Abundance Of Sirex Speciesmentioning
confidence: 99%
“…; Haavik et al. ; Sridhar and Reddy ). A variety of abiotic factors, such as temperature, humidity and photoperiod, and biotic factors influence developmental rate (Uvarov ; Krasnov et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Haavik et al. ), its simplifying assumptions are routinely neglected (but see Amendt ). For example, because DD measures the total amount of accumulated heat, how it is accumulated (e.g.…”
Section: Introductionmentioning
confidence: 99%